Nano-assembled thin film gas sensors. 1. Ammonia detection by a porphyrin-based multilayer film. - Korposh, Serhiy O.; Takahara, Naoki; Ramsden, Jeremy J.; Lee, Seung-Woo; Kunitake, Toyoki (Association of Modern Scientific Investigation, 2006)
A thin film of porphyrin deposited by the layer-by-layer method is employed as the active element for an optical sensor. The usefulness of this film technology and the resulting nanoscale matrix for the detection of volatile organic compounds (VOCs), aromatics and amine-containing substances has been studied. The sensing principle is based on monitoring the optical changes of the Q band at 700 nm, as induced by the analyte in the electrostatic interaction between tetrakis(4-sulfophenyl)porphine (TSPP) and poly(diallyldimethylammonium chloride) (PDDA) layers. Three thin film samples with different thicknesses were prepared to assess the effect of film thickness on the sensitivity. For ammonia, the sensor shows a linear sensitivity in the concentration range 0–100 ppm and the sensor response was within 30 seconds. Sensor response could be regenerated by rinsing in distilled water.
Keywords: ammonia detection; layer-by-layer; optical fibres; porphyrin; thin film gas sensor